Social STEAM Maker, do digital ao barro: tecnologia social, integrativa e prática para o ensino médio - Costa, Márcia Maria Arco e Flexa Ferreira da (2020)
The objective of this thesis was to reflect on a conceptual and practical alternative for education in digital technological times that would serve the school and the market. For this reflection, the following questions were answered with a focus on High School: "Can an integrated, practical and carried out methodology with everyone be a differential for education in the technological age?"; "Does a methodology based on the concept of STEAM, under the bias of practical learning (Maker), solidary, critical and collaborative (Social), prove to be relevant for education?". The result was positive for both questions, corroborating the construction and validation of the Social STEAM Maker (SSM) concept. Answers were found that pointed to an accessible, integrated and practical education alternative under the axis of science, technology, engineering, arts and mathematics, justified by the importance of equipping schools, students and teachers to understand a teaching offered to all; Integrated with disciplines, themes and markets, within a global, accelerated and hyperconnected technological context that transforms lives, work and relationships. The research is inserted in the contemporary educational context of Brazil, and in the technological scope of the National Common Curricular Base. Methodologically cartographic, the research, in its dynamic action, made use of clay as an integrating resource and the construction of the Teles Educational Lathe, electric and digital (to model clay), as a product of the thesis. The concept of Social STEAM Maker was materialized and validated through connectable and modifiable steps based on three axes that positively confirmed the research questions. The first of theoretical reflection and conceptualization; the second of deepening the clay as a resource and building the lathe; the third, validation of the SSM concept, through dialogues, experiments, workshops and quantitative questionnaires in the public and private spheres and within different audiences. The theoretical foundation is based on reflections on social technology; in the STEAM premises of Georgette Yakman and in the concepts of the Maker Culture, having a general basis in the theses of education of Comenius. The research culminated in a solidary, digital and face-to-face exhibition, in which ceramic pieces made in the Teles Educational Lathe were purchased and the value of each piece was defined by the buyer and deposited directly to the CENA Mission, an institution that serves vulnerable people, in Cracolândia, in São Paulo, showing the possibility of an education with social, integrated and practical relevance.